Development of Project Based Psychomotor Assessment Instruments to Measure Student Learning Outcomes in Marketing Subjects on Basic Competencies of Marketing Mix - Eva Rosita Dewi; Wening Patmi Rahayu (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This study aimed to produce a project-based psychomotor assessment instrument in accordance with the 2013 curriculum, on Marketing Mix Competence and to measure student learning outcomes. A research method that was used in this article is Research and Development (R&D). The data was obtained from validation experts, students' understanding of 12 students, as well as student learning outcomes. The validation result of the contents of psychomotor assessment instruments by expert validators which consist of 1 lecturer and 2 teachers are 94 percent and 92.8 percent. Meanwhile, validation of the project by expert validators is about 95 percent and 93.8 percent, respectively. The results of readability test (comprehension) obtained by the students of tenth-grade of Online Business and Marketing Expertise class with 90.2 percent. While the results of student learning in the product label sketch with an average final score of 3.82. Based on the results of content validation and readability test it can be concluded that the project-based psychomotor assessment instrument to measure student learning outcomes is feasible to be used in the teaching-learning process.